THE RELATIONSHIP BETWEEN SELF-CONCEPT AND PEER INTERACTION WITH FoMO LEVELS IN ADOLESCENTS - Riyani lintang Viona; nanang martono; Amalia Nur Ramadhani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
FoMO or Fear of Missing Out is the feeling of wanting to always be connected and not left behind with other people's activities. The FoMO phenomenon is a widespread phenomenon in society, especially among teenagers. This can be influenced by various factors, such as: self-concept and peer interaction. This study aims to explain the relationship between self-concept and peer interaction with FoMO levels in adolescents. This study uses a survey method. Data were analyzed using the Tau Kendall correlation test to measure the relationship between variables. The results showed that there was a positive relationship between self-concept and FoMO in adolescents with a correlation value of 0.14, and a p value of 0.003 showing that the two variables were significantly related. The analysis of the results of the study showed that there was a positive relationship between peer interaction and FoMO in adolescents of 0.29 with a p value of 0.000, showing that there was a significant relationship between the two variables. The results of this study show that self-concept and peer interaction are not fully related to the level of FoMO. A less positive self-concept becomes an evaluation for oneself rather than comparing it to others. Adolescents with a positive self-concept tend to experience FoMO, compared to adolescents who have a negative self-concept. Enough peer attachment cannot cause anxiety in adolescents. FoMO in adolescents focuses more on academic matters such as grades and achievements than entertainment or lifestyle.